A matemática da reforma Francisco Campos em ação no cotidiano escolar - Alvarez, Tana Giannasi (2004)
This research analyzes in what ways the changes in the teaching of Mathematics proposed by the Francisco Campos Reform, were appropriated and implemented by teachers from Gymnasium of São Paulo Capital, during 1930 s. Based on a historical perspective as far as school subject are concerned, discussed by Dominique Julia and André Chervel, and on the appropriation concept, characterized by Roger Chartier, this paper privileges the study of school archives as historical sources. By using class record rosters, tests and notebooks, besides former student s accounts, it also seeks to contribute to the history of the Mathematics Education in Brazil